HUBUNGAN AKTIVITAS FISIK TERHADAP RESTING HEART RATE REMAJA - Septianingrum, Kartika; Fitriadi, Aziz; Utomo, Andy Widhiya Bayu (Universitas Hamzanwadi, 2025)
The purpose of this study was to determine the relationship of physical activity to resting heart rate. This study used a quantitative descriptive method with a cross-sectional approach. Subjects in this research amounted to 50 students from the physical education health and recreation study program of STKIP Modern Ngawi. The sample was selected through the total sampling method. Data were analyzed descriptively and correlatively. The instrument used to collect data on the level of physical activity was the IPAQ-SF questionnaire and heart rate was measured by palpating the arterial blood vessels in the wrist and counting the number of beats per minute. The results of the resting pulse study obtained a minimum value of 41 beats per minute. Physical activity obtained a minimum value of 1122 MET-minutes / week, a maximum value of 4173 MET-minutes / week, and obtained an average of 2442.5 MET-minutes / week. The normality test using the Kolmogorov-Smirnov test shows that the significance of pulse rate p > 0.05, which is 0.63 > 0.05. The significance value of physical activity p > 0.05 which is 0.200 > 0.05. The conclusion in this study is that there is a relationship between physical activity and resting heart rate.